Augmentation of Fear Extinction by Transcranial Direct Current Stimulation (tDCS) - Dittert, Natalie; Hüttner, Sandrina; Polak, Thomas; Herrmann, Martin J. (Frontiers in Behavioral Neuroscience, 2018)
Although posttraumatic stress disorder (PTSD; DSM-V 309.82) and anxiety disorders (DSM-V 300.xx) are widely spread mental disorders, the effectiveness of their therapy is still unsatisfying. Non-invasive brain-stimulation techniques like transcranial direct current stimulation (tDCS) might be an option to improve extinction learning, which is a main functional factor of exposure-based therapy for anxiety disorders. To examine this hypothesis, we used a fear conditioning paradigm with female faces as conditioned stimuli (CS) and a 95-dB female scream as unconditioned stimuli (UCS). We aimed to perform a tDCS of the ventromedial prefrontal cortex (vmPFC), which is mainly involved in the control of extinction-processes. Therefore, we applied two 4x4 cm electrodes approximately at the EEG-positions F7 and F8 and used a direct current of 1.5 mA. The 20-minute stimulation was started during a 10-minute break between acquisition and extinction and went on overall extinction-trials. The healthy participants were randomly assigned in a double-blinded process into a sham stimulation and two verum stimulation groups with opposite current flow directions. To measure the fear reactions, we used skin conductance responses (SCR) and subjective ratings. We performed a generalized estimating equations model for the SCR to assess the impact of tDCS and current flow direction on extinction processes for all subjects that showed a successful conditioning (N = 84). The results indicate that tDCS accelerates early extinction processes with a significantly faster loss of CS+/CS- discrimination. The discrimination loss was driven by a significant decrease in reaction towards the CS+ as well as an increase in reaction towards the CS- in the tDCS verum group, whereas the sham group showed no significant reaction changes during this period. Therefore, we assume that tDCS of the vmPFC can be used to enhance early extinction processes successfully. But before it should be tested in a clinical context further investigation is needed to assess the reason for the reaction increase on CS-. If this negative side effect can be avoided, tDCS may be a tool to improve exposure-based anxiety therapies.